Electromagnetic wave absorber and manufacturing method thereof
Patent Information
- Application Number
- JP2023133366
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-03-03
AI Technical Summary
【0010】 本開示によれば、高い吸収率と熱応答性とを両立させることができる。
Smart Images

Figure 2025028514000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electromagnetic wave absorber and a method for producing the same. [Background technology]
[0002] Electromagnetic wave absorbers that absorb electromagnetic waves are used in various applications. Electromagnetic wave absorbers are materials that absorb incident electromagnetic waves by converting them into thermal energy through conductor loss, dielectric loss, or magnetic loss. In order to improve the absorption performance of electromagnetic wave absorbers, it is necessary to reduce the interface reflection component caused by the difference in the complex refractive index between air and the material.
[0003] In order to reduce the reflectance as much as possible and improve the absorption performance, various techniques have been developed (see Patent Documents 1 to 5). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-32341 [Patent Document 2] JP2014-187134A [Patent Document 3] Patent No. 5606572 [Patent Document 4] JP2015-95638A [Patent Document 5] Patent No. 6877770 Summary of the Invention [Problem to be solved by the invention]
[0005] Electromagnetic wave absorbers are used in power meters that measure the absolute value of electromagnetic wave intensity. In particular, to realize next-generation information and communication systems that use electromagnetic waves between 100 GHz and 300 GHz, there is a strong demand for power meters that can measure electromagnetic waves in the millimeter wave and terahertz wave frequency bands.
[0006] Performance characteristics that characterize a power meter include measurement accuracy and response speed. A power meter is mainly composed of an electromagnetic wave absorber and a thermoelectric conversion unit (heat detection unit), and one of the dominant factors that determines the measurement accuracy is the absorption rate of the electromagnetic wave absorber. Meanwhile, the response speed depends on the thermal responsiveness of the electromagnetic wave absorber. For this reason, there is a demand for an electromagnetic wave absorber that combines absorptivity and thermal responsiveness.
[0007] An object of the present disclosure is to provide an electromagnetic wave absorber that can achieve both high absorption rate and thermal responsiveness, and a method for producing the same. [Means for solving the problem]
[0008] An electromagnetic wave absorber according to one aspect of the present disclosure includes a hollow structure having a bottom surface, and a heat conductive layer formed continuously from an outer surface of the hollow structure to the bottom surface.
[0009] A manufacturing method for an electromagnetic wave absorber according to one embodiment of the present disclosure includes the steps of forming a hollow structure having a bottom portion using a 3D printer, and continuously forming a thermally conductive layer from the outer surface of the hollow structure to the bottom portion, and the modeling method using the 3D printer is at least one of a fused deposition modeling method, a photolithography method, a powder sintering method, and a material injection method. Effect of the Invention
[0010] According to the present disclosure, it is possible to achieve both high absorptivity and thermal responsiveness. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a diagram for explaining a first configuration example of an electromagnetic wave absorber according to the present disclosure. [Diagram 2] A graph showing the film thickness dependence of transmittance, reflectance, and absorptance when electromagnetic waves are perpendicularly incident on a metal thin film that is equal to or shorter than the electromagnetic shielding length. [Diagram 3] A cross-sectional view showing an example in which a metal plate is provided on the bottom side of an electromagnetic wave absorber. [Figure 4] FIG. 11 is a diagram for explaining a second configuration example of the electromagnetic wave absorber of the present disclosure. [Diagram 5] FIG. 1 is a diagram showing an example in which the periodic structure has a hexagonal prism shape; [Figure 6] FIG. 11 is a diagram for explaining a third configuration example of the electromagnetic wave absorber of the present disclosure. [Figure 7] FIG. 13 is a cross-sectional view for explaining a fourth configuration example of the electromagnetic wave absorber according to the present disclosure. [Figure 8] A conceptual diagram explaining the mechanism by which thermal response is improved by a thermally conductive layer formed continuously on the surface of the structure. [Figure 9] FIG. 13 shows the spectrum and noise level of a reflected pulse signal measured by placing a gold mirror on a stage on which an electromagnetic wave absorber is placed. [Figure 10] Schematic diagram of the measurement system used to evaluate thermal response [Figure 11] Illustrates an optical microscope image of sample 1. [Figure 12] Graph showing the reflection characteristics of Sample 1 before and after the formation of a thermally conductive layer [Figure 13] Graph showing the thermal response characteristics of Sample 1 before and after the formation of a thermally conductive layer [Figure 14] Photographs of Comparative Example 1 and Sample 1 [Figure 15] FIG. 1 is a diagram showing the measurement results of infrared emissivity of Comparative Example 1. [Figure 16] FIG. 1 shows the measurement results of reflectance obtained by time domain spectroscopy. [Figure 17] 1 shows snapshots taken during infrared camera measurement of Sample 1 and Comparative Example 1. [Figure 18] A plot of the temperature rise over time at the center of Sample 1 and Comparative Example 1. [Figure 19] Optical microscope image of sample 2 [Figure 20] Graph showing frequency dependence of reflectance of sample 2 after forming a 132 nm thermal conductive layer [Figure 21] The figure shows the time response when the maximum temperature rise value is set to 1 for sample 2 before and after the formation of the thermal conductive layer. [Figure 22]Optical microscope image of sample 3 [Diagram 23] Optical microscope image of sample 4 [Figure 24] Illustrates an optical microscope image of Sample 5. [Diagram 25] A diagram summarizing the comparison results between samples DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. However, more detailed explanation than necessary, for example, detailed explanation of already well-known matters and duplicate explanation of substantially the same configuration, may be omitted.
[0013] <First configuration example> First, a first configuration example of the electromagnetic wave absorber 1 according to the present disclosure will be described. Fig. 1 is a diagram for explaining the first configuration example of the electromagnetic wave absorber according to the present disclosure.
[0014] 1A is a diagram showing an example of the appearance of a first configuration example of an electromagnetic wave absorber 1 according to the present disclosure. The electromagnetic wave absorber 1 has a hollow periodic structure 11 formed along a predetermined xy plane, and a heat conduction layer 12 formed continuously from the outer surface of the periodic structure 11, through the inner surface, to a bottom part B of the periodic structure 11. In other words, the electromagnetic wave absorber 1 is configured by arranging a plurality of periodic structures 11 side by side along the xy plane.
[0015] In the first configuration example, the periodic structure 11 is a quadrangular pyramid-shaped structure, and an opening 111 is provided on the side surface of the periodic structure 11. The outer surface of the periodic structure 11 means the side surface of the quadrangular pyramid shape, and the inner surface of the periodic structure 11 means the surface constituting a hollow structure provided inside the quadrangular pyramid shape. The bottom surface part B of the periodic structure 11 is disposed on the xy plane. A space 112 is provided inside the periodic structure 11. The electromagnetic wave absorber 1 may be disposed within an angle range of, for example, ±30 degrees with respect to the incident direction of the electromagnetic wave, but the installation angle of the electromagnetic wave absorber is not limited to that angle in the present disclosure.
[0016] FIG. 1B is a cross-sectional view (partial) of the electromagnetic wave absorber 1 in a plane perpendicular to the xy plane, including the vertices of the plurality of periodic structures 11.
[0017] As shown in FIG. 1B, the periodic structures 11 are arranged at the same period p in the x direction and the y direction. In the example shown in FIG. 1B, the width of the periodic structure 11 for one period (the length along the x direction or the y direction) and the length p of one period are the same length, but the present disclosure is not limited to this. For example, the width of the periodic structure 11 may be smaller than the length of the period p. In other words, a gap may be provided between adjacent periodic structures 11.
[0018] When the minimum wavelength of the electromagnetic wave incident on the electromagnetic wave absorber 1 is λmin, the length p of one period is represented by the following formula (1). p < 10λmin (1)
[0019] Note that λmin < p < 10λmin is called the resonance domain, and higher-order diffracted light can be generated when an electromagnetic wave is incident.
[0020] More preferably, the value of p is represented by the following formula (2). (λmin / 4) ≤ p ≤ λmin (2) p ≤ λmin is called the sub-wavelength region, and it is known that higher-order diffracted light is less likely to be generated in this region. Therefore, from the viewpoint of easily performing specific evaluation of the electromagnetic wave absorber 1, the period p of the periodic structure 11 is more preferably set in the sub-wavelength region.
[0021] Note that more preferably, the period p is represented by the following formula (3). p = (λmin / 4) (3) For example, when the minimum wavelength is 3 mm (the highest frequency is 100 GHz), the more preferable value of the period p is 750 μm.
[0022] The number of periodic structures 11 arranged side by side in the x and y directions is preferably adjusted to a length equal to or greater than the diffraction limit when the electromagnetic wave absorber 1 is used in combination with a lens, a mirror, etc. For example, when the maximum wavelength of the electromagnetic wave incident on the electromagnetic wave absorber 1 is λmax, the length of one side of the electromagnetic wave absorber 1 is preferably set to 3λmax or greater.
[0023] Although FIG. 1 shows an example in which the length of one period in the x direction is the same as that in the y direction, different periods may be set in the x direction and the y direction as long as the formula (2) is satisfied.
[0024] The height h from the bottom surface B (xy plane) of the periodic structure 11 to the top is expressed by the following formula (4). h≧(λmax / 4) (4)
[0025] More preferably, it is represented by the following formula (5). (λmax / 2) <h≦λmax (5)
[0026] For example, when the maximum wavelength of the electromagnetic wave is 3 mm (minimum frequency 100 GHz), the height h of the periodic structure 11 is preferably 1.5 mm or more and 3.0 mm or less. The heights of the periodic structures 11 constituting the electromagnetic wave absorber 1 are preferably uniform, but may not be uniform as long as they are within the ranges of formulas (4) and (5). By setting the height in this manner, the electromagnetic wave absorber 1 can achieve a high absorption rate.
[0027] As shown in FIG. 1B, the thickness d of the periodic structure 11 is preferably selected from the range of (λmin / 15) or more and λmin or less, but may be smaller than (λmin / 15). For example, when λmin=300 μm (maximum frequency 1 THz), the thickness d of the periodic structure 11 is preferably selected from the range of 20 μm or more and 300 μm or less, but may be smaller than 20 μm. The thickness d is preferably uniform throughout the structure, but does not have to be uniform as long as it is within the above range. Also, as shown in FIG. 1B, the pyramidal bottom portion B of the periodic structure 11 has a predetermined thickness t, and t is preferably 200 μm or more. Such a shape can improve the physical strength against bending.
[0028] 1, the periodic structure 11 has a quadrangular pyramid shape, but may have a triangular pyramid shape, a pentagonal pyramid shape, a hexagonal pyramid shape, or a cone shape. The shape of the space 112 provided inside the periodic structure 11 may be the same as the quadrangular pyramid shape, which is the external structure of the periodic structure 11, or may have another shape. The external shape of the periodic structure 11 and the shape of the internal space 112 may be a combination of different shapes.
[0029] 1B, the cross-sectional shape of the periodic structure 11 may be a structure that is linearly inclined from the bottom surface B to the top, but may also be another shape. For example, the cross-sectional shape may be a bullet shape that is inclined quadratically, or a Mount Fuji shape that is inclined exponentially.
[0030] The tip shape of the periodic structure 11 is pointed in the example shown in FIG. 1B, but may be other shapes. For example, it may be spherical or flat. If it is spherical, it is preferable that the diameter of the tip is formed within 10 / λmin when the minimum wavelength of the target electromagnetic wave band is λmin. The top may also be flat, and in this case, it is preferable that the length of one side is formed within 10 / λmin. With such a configuration, it is possible to reduce the reflectance of the electromagnetic wave absorber while improving its physical durability.
[0031] From the viewpoint of heat capacity, it is preferable that the area ΔS1 of the openings 111 provided on the side surface of the periodic structure 11 has a large area occupancy rate on the side surface. However, in consideration of the absorptance, it is preferable that the occupancy rate of the total area of the openings 111 (4×ΔS1 in the case of FIG. 1B) in the entire area of the side surface of one periodic structure 11 is 0% or more and 30% or less.
[0032] 1B, the shape of the opening 111 is triangular, but it may be another shape. The shape of the opening 111 may be, for example, a polygon such as a rectangle or a pentagon, a circle, or an ellipse. The shapes of the openings 111 of the multiple periodic structures 11 may be different from one another.
[0033] On the side surface of the periodic structure 11, the position where the openings 111 are provided is preferably from the top of the periodic structure 11 to near the center of the side surface. The reason for this is that a high absorptance can be achieved while keeping the heat capacity small. However, the location of the openings 111 is not limited to the above example.
[0034] By having the periodic structure 11 have such a shape, the cross-sectional area of the periodic structure 11 parallel to the bottom surface B (xy plane) continuously decreases from the bottom surface B to the top. As a result, it is known that the periodic structure 11 having such a shape behaves, with respect to the absorption of electromagnetic waves, like a multilayer film whose equivalent complex refractive index changes according to the cross-sectional area parallel to the bottom surface. For this reason, such a periodic structure 11 can reduce the reflection loss caused by the periodic structure 11, and can provide an electromagnetic wave absorber 1 with an extremely high absorption rate of electromagnetic waves.
[0035] The periodic structure 11 described above is not particularly limited as long as it is made of a material that does not reflect the target electromagnetic wave with high reflectance, and is formed of, for example, a material that satisfies the following formula (6). (1 / ρ) / (2πεf)≦100 (6) Here, ρ is the volume resistivity of the material, ε is the dielectric constant of the material, and f is the frequency of the electromagnetic wave.
[0036] Examples of such materials include amorphous thermoplastic resins such as polymethyl methacrylate resin, polycarbonate resin, polystyrene resin, cycloolefin polymer resin, cross-linked polyethylene resin, polyvinyl chloride resin, polyarylate resin, polyphenylene ether resin, modified polyphenylene ether resin, polyetherimide resin, polyethersulfone resin, polysulfone resin, and polyetherketone resin, polyethylene terephthalate, polyethylene naphthalate resin, polyethylene resin, polypropylene resin, polypropylene resin, polybutylene terephthalate resin, and aromatic polyolefin resins. Examples of the material include crystalline thermoplastic resins such as polyester resin, polyacetal resin, and polyamide resin, ultraviolet curing resins and thermosetting resins such as acrylic resin, epoxy resin, urethane resin, phenol resin, urea resin, melamine resin, and unsaturated polyester, organic base materials such as triacetate resin, and inorganic materials such as alumina, zirconia, aluminum nitride, silicon carbide, silicon nitride, forsterite, cordierite, sialon, machinable ceramics, barium titanate, lead zirconate titanate, ferrite, mullite, silicon, diamond, sapphire, and glass. In addition to highly thermally conductive resins containing inorganic minerals, composite materials within the range of effective physical properties such as antistatic resins containing carbon, alumina, metal particles, and metal fibers may also be used. From the viewpoint of manufacturability, a single layer is preferable, but a multi-layer structure may be used to impart functionality such as improved environmental resistance and improved mechanical strength, and a part of the structure may be composed of different materials.
[0037] The thermally conductive layer 12 is a film formed on the surface of the periodic structure 11. Here, the surface of the periodic structure 11 means the outer surface of the periodic structure 11, i.e., the side surface excluding the openings 111 of the pyramidal structure, and the inner surface of the periodic structure 11, i.e., the surface forming the space 112 provided inside the periodic structure 11. The thermally conductive layer 12 is disposed so as to be connected to a heat detection unit not shown in FIG. 1. The heat detection unit is an external component for detecting the intensity of the electromagnetic wave absorbed by the electromagnetic wave absorber 1 by detecting the heat energy generated when the energy of the incident wave is converted into heat energy by the electromagnetic wave absorber 1.
[0038] The thermally conductive layer 12 is continuously formed on the outer and inner surfaces of the periodic structure 11. In this specification, "the thermally conductive layer 12 is continuously formed" means that heat given to a part of the thermally conductive layer 12 formed on the surface of the periodic structure 11 can be conducted to the entire thermally conductive layer 12. Such a thermally conductive layer 12 allows the periodic structure 11 to absorb electromagnetic waves incident from the top side of the periodic structure 11 and convert them into thermal energy, and the thermal energy can be quickly transmitted to the heat detection unit by the thermally conductive layer 12. This makes it possible to obtain an electromagnetic wave absorber 1 with high thermal responsiveness.
[0039] The thermally conductive layer 12 is made of, for example, a metal. The thermal conductivity of the thermally conductive layer is preferably at least one order of magnitude, and more preferably at least two orders of magnitude, greater than the thermal conductivity of the base material constituting the periodic structure 11. For example, when the periodic structure 11 is made of a resin, the typical thermal conductivity of the resin is about 0.1 W / mK, so that the thermal conductivity of the thermally conductive layer 12 is preferably 1 W / mK or more, and more preferably 10 W / mK or more.
[0040] The material of the thermally conductive layer 12 can be selected from, for example, metal materials such as aluminum, nickel, chromium, platinum, palladium, titanium, tungsten, iron, zinc, magnesium, tin, gold, silver, copper, etc., alloy materials such as nichrome, indium tin oxide, nickel-phosphorus, nickel-boron, etc., ceramics such as alumina and silicon carbide, nitrides such as aluminum nitride, oxides such as silicon carbide and silicon dioxide, carbon-based materials such as diamond, silicon, etc. The thickness of the thermally conductive layer 12 is preferably 100 μm or less, more preferably 10 μm or less, and even more preferably 1 μm or less.
[0041] In order to utilize the thermally conductive layer 12 as a highly thermally conductive layer and an absorption layer with high absorptivity, the thermally conductive layer 12 formed on the outer surface of the periodic structure 11 is preferably made of a metal material that satisfies formula (7). (1 / ρ) / (2πεf)>100 (7)
[0042] In order to satisfy formula (7), for example, the material of the thermal conduction layer 12 must be a metal such as aluminum, nickel, chromium, platinum, palladium, titanium, tungsten, iron, zinc, magnesium, tin, gold, silver, or copper, or an alloy such as nichrome, indium tin oxide, nickel-phosphorus, or nickel-boron, and the thickness of the layer must be thinner than the electromagnetic shielding length δ expressed by formula (8).
number
[0043] For metal thin films that are shorter than the electromagnetic shielding length, the thickness at which the absorption rate is maximum varies depending on the volume resistivity. Figure 2 is a graph showing the film thickness dependence of the transmittance, reflectance, and absorption rate when an electromagnetic wave is perpendicularly incident on a metal thin film that is shorter than the electromagnetic shielding length. Figure 2 was created by calculation with reference to Non-Patent Document 1 [LN Hadley, DM Dennison, J. Opt. Soc. Am. 1947, 37, 451].
[0044] Figure 2A shows the case where ρ = 0.1 μΩm, Figure 2B shows the case where ρ = 1 μΩm, and Figure 2C shows the case where ρ = 10 μΩm. Figure 2 shows that the absorption is maximized at the film thickness where the reflectance and transmittance values are equal according to the law of conservation of energy, and that the maximum value is 50%.
[0045] Examples of metal materials with ρ=0.1 μΩm include pure metal materials such as aluminum, chromium, nickel, etc. When using these materials as the thermally conductive layer 12, the absorption rate can be maximized by setting the film thickness to 0.5 nm±0.35 nm.
[0046] In addition, examples of metal materials with ρ=1 μΩm include alloys such as nichrome and indium tin oxide. When using these materials for the thermally conductive layer 12, the thickness should be set to the range of 5 nm±3.5 nm to maximize the absorptance.
[0047] Furthermore, examples of metal materials with ρ=10 μΩm or more include alloys such as Ni-P (Ni content 91% to 93%, P content 7% to 9%). When using a material with ρ=10 μΩm as the thermal conduction layer 12, the film thickness should be set in the range of 50 nm±35 nm to maximize the absorptance.
[0048] As shown in FIG. 2B, the maximum absorptance can be achieved within a range of 5 nm±3.5 nm, but the reflectance and transmittance vary by about 20% of the total when the deviation from 5 nm by 3.5 nm occurs. For this reason, from the viewpoint of expanding the allowable range of the film thickness at which optimal optical properties are obtained, it is more desirable to use a material with a ρ larger than ρ=1 μΩm shown in FIG. 2 as the thermal conduction layer 12. Specifically, as shown in FIG. 2C, a material with a ρ=10 μΩm or more is preferable. For example, when a Ni-P plating film is used as the thermal conduction layer 12, the volume resistivity of the Ni-P plating film is about ρ=30 μΩm, so the film thickness at which good optical properties are obtained can be selected from the range of 90 nm to 180 nm. In this way, by using an alloy material with a ρ larger than ρ=10 μΩm as the thermal conduction layer 12, the range of film thickness selection is widened, and therefore the thermal conduction layer 12 with good optical properties can be formed more easily.
[0049] The thermally conductive layer 12 is preferably formed uniformly over the entire surface of the periodic structure 11, but as long as it is formed continuously, it may be formed partially on the surface of the periodic structure 11. In addition, the film thickness does not have to be uniform as long as it is within the above range.
[0050] When the electromagnetic wave absorber 1 is used for something other than a power meter, a metal plate 13 may be further provided as shown in Fig. 3. Fig. 3 is a cross-sectional view showing an example in which a metal plate 13 is provided on the bottom side of the electromagnetic wave absorber 1. The metal plate 13 is provided so as to be in contact with the heat conductive layer 12 formed on the surface of the bottom part B of the periodic structure 11.
[0051] The metal plate 13 can reflect components of the electromagnetic waves incident from a direction opposite to the xy plane of the periodic structure 11 that are not completely absorbed by the periodic structure 11 and the thermally conductive layer 12. This allows the reflected components to be absorbed again by the periodic structure 11 and the thermally conductive layer 12, maximizing the absorption rate of the electromagnetic wave absorber 1.
[0052] It is preferable that the metal plate 13 reflects 100% of the electromagnetic waves. For this reason, it is preferable that the metal plate 13 is made of a material having a thickness equal to or greater than the above-mentioned formula (8). Examples of materials for the metal plate 13 include aluminum, nickel, chromium, platinum, palladium, titanium, tungsten, iron, zinc, magnesium, tin, gold, silver, and copper. For example, when copper having a target minimum frequency of 100 GHz and a volume resistivity ρ=0.02 μΩm is used as the metal plate 13, the thickness is preferably 210 nm or more according to formula (8), and the metal plate 13 may be, for example, a copper foil having a thickness of 20 μm. However, the thickness of the metal plate 13 is not particularly limited.
[0053] The adhesive layer 131 between the periodic structure 11 and the heat conductive layer 12 and the metal plate 13 may be appropriately selected from an epoxy adhesive, a heat dissipation adhesive, a heat conductive grease, a conductive adhesive, a solder, and the like.
[0054] <Second configuration example> Next, a second configuration example of the electromagnetic wave absorber 1 of the present disclosure will be described. Fig. 4 is a diagram for explaining the second configuration example of the electromagnetic wave absorber 1 of the present disclosure.
[0055] In the second configuration example as well, the electromagnetic wave absorber 1 has a periodic structure 11 and a heat conductive layer 12. Fig. 4A is a perspective view of the electromagnetic wave absorber 1 of the second configuration example. In the second configuration example, as shown in Fig. 4A, the periodic structure 11 is a columnar structure oriented in a direction perpendicular to the xy plane, and the columnar structures, each having an opening 111 on its bottom surface (upper bottom surface) facing the xy plane, are periodically arranged along the xy plane. Fig. 4B is a top view of the electromagnetic wave absorber 1 of the second configuration example.
[0056] In Fig. 4A, the periodic structure 11 has a cylindrical shape, but the present disclosure is not limited to this, and may have, for example, a rectangular prism shape. Fig. 5 is a diagram showing an example in which the periodic structure 11 has a hexagonal prism shape. Fig. 5A and Fig. 5B are a perspective view and a top view, respectively, of the electromagnetic wave absorber 1 in which the periodic structure 11 has a hexagonal prism shape.
[0057] The period p at which the periodic structure 11 is provided may be expressed by the following formulas (1) and (2), and more preferably by formula (3), similarly to the first configuration example. p≦λmin (1) (λmin / 4)≦p≦λmin (2) p = (λmin / 4) (3)
[0058] Moreover, by setting the height h from the bottom surface B (xy plane) of the periodic structure 11 to the top to satisfy the following formula (4) as in the first configuration example, the electromagnetic wave absorber 1 can achieve a high absorption rate. However, in the second configuration example, since the cross-sectional area parallel to the bottom surface does not change depending on the height, in order to achieve a higher absorption rate, it is preferable to make the height larger as shown in formula (5). h≧(λmax / 4) (4) (λmax) <h≦2λmax (5)
[0059] The thermally conductive layer 12 is continuously formed on the edge portion of the upper surface and the side surfaces (outer surface and inner surface) of the cylindrical periodic structure 11. This allows the electromagnetic wave absorber 1 of the second configuration example to suitably absorb electromagnetic waves, similar to the first configuration example.
[0060] <Third configuration example> Next, a third configuration example of the electromagnetic wave absorber 1 of the present disclosure will be described. Fig. 6 is a diagram for explaining the third configuration example of the electromagnetic wave absorber 1 of the present disclosure.
[0061] In the third configuration example as well, the electromagnetic wave absorber 1 has a periodic structure 11 and a thermally conductive layer 12. The third configuration example shows an example in which a lattice structure extending not only in the direction along the xy plane but also in the height direction is provided as the periodic structure 11.
[0062] The period p and height h of the periodic structure 11 may be set in the same manner as in the first and second configuration examples.
[0063] The thermally conductive layer 12 is formed continuously over the entire surface of the lattice-like framework of the periodic structure 11. This allows the electromagnetic wave absorber 1 of the third configuration example to suitably absorb electromagnetic waves, similar to the first and second configuration examples.
[0064] <Fourth configuration example> Next, a fourth configuration example of the electromagnetic wave absorber 1 of the present disclosure will be described. Fig. 7 is a cross-sectional view for explaining the fourth configuration example of the electromagnetic wave absorber 1 of the present disclosure.
[0065] The electromagnetic wave absorber 1 of the fourth configuration example has a spherical or cylindrical hollow structure 14 with a circular cross section, a first thermally conductive layer 15 formed on the surface of the hollow structure 14, and a second thermally conductive layer 16 disposed on the bottom surface part B of the hollow structure 14 and formed continuously with the first thermally conductive layer 15. The hollow structure 14 is, for example, an integrating sphere.
[0066] The hollow structure 14 has an opening 141 at a position opposite to the bottom surface portion B. The electromagnetic wave incident on the electromagnetic wave absorber 1 is collected by the collector 100 and enters the inside of the hollow structure 14 from the opening 141. As the collector 100, a Winston cone, a parabolic mirror, or the like may be used.
[0067] Fig. 7A shows an example in which the first thermally conductive layer 15 is formed only on the outer surface of the hollow structure 14. Also, in Fig. 7A, the optical path of the electromagnetic wave incident from the collector 100 is shown by a solid arrow.
[0068] As indicated by the arrows in Fig. 7A, the electromagnetic waves collected by the collector 100 and incident on the inside of the hollow structure 14 are partly absorbed by the hollow structure 14, and the remainder is reflected by the surface (inner surface) of the hollow structure 14. As a result, the electromagnetic waves are reflected inside the hollow structure 14 until all of the incident electromagnetic waves are absorbed, so that the electromagnetic wave absorber 1 can have an extremely high absorption rate of the electromagnetic waves.
[0069] The electromagnetic waves absorbed by the hollow structure 14 are converted into thermal energy and transmitted to the first thermally conductive layer 15, and further transmitted to the second thermally conductive layer 16 via the first thermally conductive layer 15. The second thermally conductive layer 16 is connected to a heat detection unit (not shown). This allows the electromagnetic wave absorber 1 to have high thermal responsiveness.
[0070] As shown in Fig. 7B, the hollow structure 14 may simply function as a framework, and the front surface of the hollow structure 14 may be covered with the first thermally conductive layer 15. Even in this case, as in the example shown in Fig. 7A, it is possible to obtain an electromagnetic wave absorber 1 having a very high absorptivity and high thermal responsiveness.
[0071] <Action and effect> The following describes the action and effect of the electromagnetic wave absorber of the above-mentioned configuration example. As described above, the electromagnetic wave absorber 1 according to the present disclosure is characterized in that a heat conductive layer (heat conductive layer 12, or first heat conductive layer 15 and second heat conductive layer 16) is continuously formed on the surface (outer surface and inner surface) of the hollow structure (periodic structure 11, or hollow structure 14).
[0072] FIG. 8 is a conceptual diagram for explaining the mechanism by which thermal responsiveness is improved by a thermally conductive layer continuously formed on the surface of a structure. FIG. 8A illustrates a structure 200 in which a thermally conductive layer 202 is formed on the surface of a resin layer 201. A heat detection unit 300 is provided as an external configuration at the ends of the resin layer 201 and the thermally conductive layer 202. Here, the thermally conductive layer 202 is a thin film having a higher thermal conductivity and a smaller heat capacity (=specific gravity×specific heat×volume) than the resin layer 201. The difference in thermal conductivity between the resin layer 201 and the thermally conductive layer 202 is effective if it is 10 times or more, and preferably 100 times or more.
[0073] When electromagnetic waves are locally irradiated onto structure 200 from the resin layer 201 side, the thermal energy diffusion path is as shown in Fig. 8B. First, the thermal energy generated on the surface of resin layer 201 irradiated with electromagnetic waves is isotropically diffused from the thickness direction to the in-plane direction, and transferred to thermally conductive layer 202. At this time, since the thermal capacity of thermally conductive layer 202 is smaller than that of resin layer 201, even a relatively small amount of thermal energy causes a relatively large local temperature rise.
[0074] According to Fourier's law, thermal energy is transferred in the direction in which a temperature gradient occurs, and the magnitude of the transferred thermal energy is proportional to the thermal conductivity of a substance, so that the thermal energy generated in thermally conductive layer 202 flows through thermally conductive layer 202, which has a higher thermal conductivity, rather than through resin layer 201. As a result, the temperature of the entire thermally conductive layer 202 rises faster than the temperature rise of the entire structure 200, so that the thermal energy generated by the absorption of electromagnetic waves in structure 200 is quickly detected by heat detection unit 300 via thermally conductive layer 202.
[0075] In this manner, by providing the thermally conductive layer 202 having a higher thermal conductivity on the surface of the resin layer 201, the structure 200 can have a high thermal responsiveness.
[0076] As shown in FIG. 8C, when electromagnetic waves are applied from the thermal conductive layer 202 side, the thermal energy generated by the thermal conductive layer 202 absorbing the electromagnetic waves is diffused quickly within the thermal conductive layer 202, which has high thermal conductivity. Therefore, since the resin layer 201 is not involved, the thermal detection unit 300 can detect heat more quickly than the thermal diffusion process illustrated in FIG. 8B.
[0077] In all of the first to fourth configuration examples of the electromagnetic wave absorber 1 described above, the thermal energy generated by absorbing the incident electromagnetic waves can be rapidly transferred to the heat detection unit by the thermally conductive layer continuously formed on the surface of the hollow structure. This allows the electromagnetic wave absorber 1 to have high thermal responsiveness.
[0078] Moreover, in the electromagnetic wave absorber 1 of the first configuration example, a periodic structure 11 having a pyramidal shape is formed as a hollow structure. In this way, a structure in which the cross-sectional area parallel to the bottom changes from the apex to the bottom is known to behave like a multilayer film in which the complex refractive index changes linearly in relation to the reflectance equivalently in response to the change in the cross-sectional area, when the height of the pyramidal shape is set to a size of about the wavelength of the electromagnetic wave and the arrangement period of the periodic structure 11 is made smaller than the wavelength of the electromagnetic wave. This makes it possible to achieve a low reflectance, and as a result, a high absorptance.
[0079] It is also known that a low reflectance can be achieved with a columnar material group oriented perpendicular to the xy plane, a honeycomb structure, or a three-dimensional structure in which branched materials are periodically arranged, such as a lattice structure. For this reason, the second and third configuration examples also use a cylindrical structure, a hexagonal columnar structure, and a lattice structure as the hollow structure 14, thereby achieving a low reflectance and, as a result, a high absorptance.
[0080] Furthermore, in a structure such as the fourth configuration example, in which the electromagnetic wave incident from the opening is confined within a spherical or cylindrical hollow structure 14 and the components that cannot be absorbed are repeatedly totally reflected, a very high absorption rate can be achieved.
[0081] From the above, the electromagnetic wave absorber 1 according to the present disclosure can rapidly increase the temperature of the entire electromagnetic wave absorber 1 by the heat conductive layer continuously formed on the surface of the hollow structure. Therefore, even if the hollow structure is made of a material with poor thermal response, the heat conductive layer can realize a high absorption rate in a wide band and improve the thermal response. Therefore, the electromagnetic wave absorbers according to the present disclosure shown in the first to fourth configuration examples can achieve both high thermal response and high absorption rate.
[0082] <Manufacturing method> A method for producing the electromagnetic wave absorber 1 of the present disclosure will now be described.
[0083] The hollow structure (periodic structure 11 or hollow structure 14) constituting the electromagnetic wave absorber may be formed, for example, by a 3D printer using a stereolithography method (SLA method). A metal thin film layer may be continuously formed on the surface (outer surface and inner surface) of the hollow structure thus formed, for example, by electroless plating.
[0084] The modeling method of the 3D printer is preferably a stereolithography method that allows high-precision and high-speed modeling, but in this disclosure, it is not limited to the stereolithography method and can be selected from known modeling methods. Examples other than the stereolithography method include fused deposition modeling (FDM / FFF method), selective laser sintering (SLS method), and material jetting (inkjet type).
[0085] As a method for forming the thin metal film, other known techniques such as a vacuum film forming method can be used in addition to the electroless plating method.
[0086] In this way, the electromagnetic wave absorber 1 of the present disclosure can be manufactured using a 3D printer and electroless plating, and can be manufactured cheaply and easily compared to manufacturing methods that have high manufacturing costs, such as cutting work. As a result, the present disclosure can contribute to providing an electromagnetic wave power meter with high accuracy and high measurement speed at a low cost.
[0087] <Example> In the following, the electromagnetic wave absorbers 1 of the above-mentioned respective configuration examples are actually manufactured, and the absorptance, reflectance, and thermal response of each are measured to compare the performances. The results are described below.
[0088] (1) Measurement of transmittance and reflectance If the absorption rate of electromagnetic waves is A, the reflectance is R, and the transmittance is T, then the absorption rate is defined as A = 1 - RT. The transmittance and reflectance were measured using a terahertz time-domain spectroscopy device (Otsuka Electronics Co., Ltd., TR-1000).
[0089] Using the above-mentioned spectrometer, a terahertz pulse signal was focused by a parabolic mirror and irradiated onto the electromagnetic wave absorber 1. The sample stage was set at an angle of 15 degrees, and the signal reflected by the electromagnetic wave absorber 1 was focused onto the detector via a parabolic mirror (diameter 25.4 mm, focal length 50.8 mm).
[0090] 9 is a diagram showing the spectrum and noise level of a reflected pulse signal measured by placing a gold mirror on the mounting table on which the electromagnetic wave absorber 1 is placed. The inset in the upper right corner of the figure is an enlarged view of the range from 0.1 THz to 1.0 THz, and shows that the SNR at 0.1 THz is approximately 50.
[0091] (2) Measurement of thermal response The thermal response characteristics were evaluated by detecting the change in the amount of radiated infrared light that occurs when the temperature rises due to the absorption of terahertz waves. Figure 10 shows a schematic diagram of the measurement system used to evaluate the thermal response.
[0092] In this embodiment, a 16.6 GHz signal generated by a microwave signal generator (Windfreak Technologies, SynthHD Pro (v2)) was input to a 6x multiplier (Virginia Diodes, SGX-M) to convert the signal to 100 GHz, and a conical horn antenna (Virginia Diodes, WR10CH) was attached to the output port of the multiplier to perform spatial radiation. In order to improve thermal insulation, resin was used as the material for the jig. Plastic tape was attached to a part of the electromagnetic wave absorber 1, and the tape was attached to a resin block with a hole in the center. The diameter of the opening of the horn antenna was 16.3 mm.
[0093] According to Planck's law of blackbody radiation, the wavelength of electromagnetic waves strongly radiated by an object near room temperature is between 8 μm and 14 μm. Therefore, the measurement device shown in Figure 10 detected infrared radiation using an infrared thermography camera (Avionix, Thermo FLEX F50B-ONL) that has sensitivity in this wavelength range.
[0094] [Reference Example 1: Optical properties of resin plate / Ni-P plating film] As Reference Example 1, the optical properties of a resin plate / Ni-P plating film are shown in Table 1. [Table 1]
[0095] Table 1 shows the results of transmittance and reflectance measurements when a 20 mm x 20 mm x 0.95 mm resin plate was subjected to electroless Ni-P plating after stereolithography, and also lists the approximate absorption rates calculated from these. Here, the resin plate was used as the reference signal when measuring the transmittance, and the mirror was used as the reference signal when measuring the reflectance. The transmittance and reflectance values listed are the average values between 0.1 THz and 1.0 THz. Table 1 shows that the film thickness at which the absorption rate is maximum is between approximately 100 nm and 180 nm.
[0096] [Example 1: Sample 1] In Example 1, a sample of the electromagnetic wave absorber 1 having the shape explained in the first configuration example according to the present disclosure was actually manufactured, and its characteristics were measured. Hereinafter, the electromagnetic wave absorber in this Example 1 will be referred to as Sample 1. Fig. 11 is an optical microscope image of Sample 1. Fig. 11A shows the state before the thermally conductive layer 12 is formed, and Fig. 11B shows the state after the Ni-P plating is formed as the thermally conductive layer 12.
[0097] In sample 1, the ratio of the area occupied by the openings 111 provided on the side surface of the periodic structure 11 was 30%. In sample 1, 15 periodic structures 11 were arranged in each of the x and y directions in FIG. 1. Therefore, the effective area for interaction with electromagnetic waves was 15 mm 2 x15mm 2 It is.
[0098] In Example 1, it is assumed that the sample 1 is used in a power meter, and that a metal plate serving as a heat detection unit is disposed on the bottom side of the sample 1. Therefore, the transmittance can be regarded as 0, and the absorptance can be determined by measuring the reflectance.
[0099] Figure 12 is a graph showing the reflection characteristics of Sample 1 before and after the formation of the thermally conductive layer. The thickness of the Ni-P plating film serving as the thermally conductive layer is 158 nm. Focusing on the range of 0.1 THz to 0.3 THz in Figure 12, due to the low absorption coefficient of the hollow structure (resin layer), no absorption occurs before the formation of the thermally conductive layer, and the pulse wave incident on Sample 1 is reflected by the metal plate, resulting in a reflectance of 80% to 90% for electromagnetic waves over 100 GHz. On the other hand, the reflectance after the formation of the thermally conductive layer is reduced to about 1%, and it can be seen that the absorption effect of the thermally conductive layer is large from the absorptance A = 1-R.
[0100] Table 2 shows the relationship between the thickness and reflectance of the thermally conductive layer. [Table 2]
[0101] Table 2 shows the reflection characteristics for 120 GHz electromagnetic waves as an example. If the film thickness is thin, the reflectance of the thermally conductive layer itself is low, and the absorptance is also low. On the other hand, if the film is too thick, the reflectance of the thermally conductive layer itself is too high. The highest absorptance is obtained at an intermediate film thickness. Such characteristics of Sample 1 are similar to those of the reference example (a plate-shaped Ni-P film plated). It can also be seen that the preferred film thickness of the thermally conductive layer in Table 2, 158 nm, is consistent with the optimal film thickness range of the thermally conductive layer 12 described in the above embodiment.
[0102] FIG. 13 is a graph showing the thermal response characteristics of sample 1 before and after the formation of the thermal conductive layer. As in the evaluation of the optical characteristics, a metal plate was placed as a heat detection unit on the bottom side of sample 1 to evaluate the thermal response. FIG. 13A shows the relationship between the thickness of the thermal conductive layer (without thermal conductive layer, 70 nm, 158 nm, and 246 nm) and the temperature rise. As shown in FIG. 13A, the maximum temperature rise value before the formation of the thermal conductive layer (corresponding to "without thermal conductive layer" indicated by △) is the lowest. FIG. 13B shows a graph in which the vertical axis is divided by the maximum temperature rise value. For simplicity, FIG. 13B shows the values before the formation of the thermal conductive layer (corresponding to "without thermal conductive layer") and after the formation of a thermal conductive layer with a thickness of 158 nm. According to FIG. 13B, it can be seen that the thermal time constant is improved after the formation of the thermal conductive layer compared to before the formation of the thermal conductive layer.
[0103] [Comparative Example 1: Magnetic loss epoxy described in Non-Patent Document 2] In the following, as Comparative Example 1, the optical properties and thermal response properties of an absorber (hereinafter referred to as magnetic loss epoxy) made by processing a magnetic loss material-loaded epoxy (ECCOSORB MF-117, E&C Engineering Co., Ltd.) into a pyramidal shape, as described in Non-Patent Document 2 [H. Iida et al., J. Infrared Milli. Terahz. Waves 39, 5 (2018)], are compared with those of Sample 1.
[0104] Figure 14 shows photographs of Comparative Example 1 and Sample 1. Figure 14A shows photographs of the front and back of a magnetic loss epoxy in which circular pyramid (square pyramid-shaped) structures with a diameter of 15 mm and a height of 2 mm are arranged at intervals of 0.8 mm. Figure 14B shows a photograph of a metal plate attached to the back of Sample 1, and the back of the metal plate sprayed with black body spray (Ichinen TASCO, TA410KS).
[0105] FIG. 15 is a diagram showing the measurement results of the infrared emissivity of Comparative Example 1. FIG. 15 shows the results of measuring the infrared emissivity of the magnetic loss epoxy using an infrared spectrometer from JASCO. Since the measured transmittance was equivalent to the noise level of the infrared spectrometer, FIG. 15 shows only the results of the reflectance. According to FIG. 15, it can be seen that the average emissivity in the range of 8 μm to 14 μm is about 0.94.
[0106] In order to facilitate a comparison between Sample 1 and Comparative Example 1, the average emissivity of Sample 1 was adjusted to 0.94, matching that of Comparative Example 1, by spraying a blackbody spray onto the rear surface of Sample 1.
[0107] Fig. 16 is a diagram showing the measurement results of reflectance obtained by time domain spectroscopy. It can be seen from Fig. 16 that Sample 1 according to the present disclosure achieves a low reflectance at a level equivalent to that of the magnetic loss epoxy of Comparative Example 1. Since the transmitted component of the magnetic loss epoxy is also equivalent to the noise level, the absorptance can be determined by A = 1-R.
[0108] Fig. 17 shows snapshots taken during infrared camera measurement of Sample 1 and Comparative Example 1. Fig. 17A shows a snapshot of Sample 1, and Fig. 17B shows a snapshot of Comparative Example 1.
[0109] 18 is a plot of the temperature rise over time at the center (corresponding to point P1 in FIGS. 17A and 17B) of Sample 1 and Comparative Example 1. The 90% thermal time constant is calculated based on FIG. 18 to be 100 seconds for Sample 1 and 300 seconds for the magnetic loss epoxy. This shows that the thermal time constant of Sample 1 according to the present disclosure is three times better than that of Comparative Example 1.
[0110] Here, the above-mentioned Non-Patent Document 2 discloses an absorber having high-speed thermal response using isothermal control. Considering that the response time of the magnetic loss epoxy disclosed in Non-Patent Document 2 is 70 seconds, the response time of Sample 1 is 23 seconds, and when used as a power meter, a very short rise time can be realized.
[0111] [Example 2: Sample 2] In Example 2, a sample in which the openings 111 were not provided on the side surface of the periodic structure 11 in the first configuration example was actually manufactured, and its characteristics were measured. Hereinafter, the electromagnetic wave absorber 1 in Example 2 will be referred to as Sample 2. FIG. 19 is an optical microscope image of Sample 2. FIG. 19A shows the state before the thermally conductive layer 12 is formed, and FIG. 19B shows the state after the Ni-P plating is formed as the thermally conductive layer 12. The size of Sample 2 is different from that of Sample 1.
[0112] In sample 2, as in sample 1, 15 periodic structures 11 are arranged in each of the x and y directions, so that the effective area for interaction with electromagnetic waves is 15 mm 2 x15mm 2 It is.
[0113] Fig. 20 is a diagram showing the frequency dependence of the reflectance of Sample 2 after forming a 132 nm thermally conductive layer. As shown in Fig. 20, the maximum reflectance was 2.4 at 120 GHz.
[0114] Fig. 21 is a diagram showing the time response of Sample 2 before and after the formation of the thermally conductive layer, when the maximum temperature rise value is set to 1. The thickness of the thermally conductive layer in Fig. 20 is 132 nm. According to Fig. 21, the 90% thermal time constant after the formation of the thermally conductive layer is 100 seconds, while the thermal time constant before the formation of the thermally conductive layer is 180 seconds, and it is clear that the time constant is improved by the formation of the thermally conductive layer.
[0115] [Example 3: Sample 3] In Example 3, a sample in which the openings 111 were not provided on the side surface of the periodic structure 11 in the first configuration example and which had a size different from that of Sample 2 was actually manufactured and its characteristics were measured. Hereinafter, the electromagnetic wave absorber 1 in Example 3 will be referred to as Sample 3. Fig. 22 is an optical microscope image of Sample 3. Fig. 22A shows the state before the thermally conductive layer 12 was formed, and Fig. 22B shows the state after the Ni-P plating was formed as the thermally conductive layer 12.
[0116] In sample 3, 15 periodic structures 11 are arranged in each of the x and y directions. Since the size of the periodic structures 11 is different from that of samples 1 and 2, the effective area for interaction with electromagnetic waves is 16 mm 2 x16mm 2 It is as follows.
[0117] [Example 4: Sample 4] In Example 4, a sample of a different size from Sample 1 in the first configuration example was actually manufactured, and its characteristics were measured. Hereinafter, the electromagnetic wave absorber 1 in Example 4 will be referred to as Sample 4. FIG. 23 is an optical microscope image of Sample 4. FIG. 23A shows the state before the thermally conductive layer 12 is formed, and FIG. 23B shows the state after the Ni-P plating is formed as the thermally conductive layer 12. The size of Sample 4 is different from that of Sample 1.
[0118] In sample 4, as in samples 1 and 2, 15 periodic structures 11 are arranged in each of the x and y directions, so that the effective area for interaction with electromagnetic waves is 15 mm 2 x15mm 2 It is.
[0119] [Example 5: Sample 5] In Example 5, a sample in which the opening 111 and the space 112 in the first configuration example were not provided was actually manufactured, and its characteristics were measured. Hereinafter, the electromagnetic wave absorber 1 in Example 5 will be referred to as Sample 5. FIG. 24 is an optical microscope image of Sample 4. FIG. 24A shows the state before the thermally conductive layer 12 is formed, and FIG. 24B shows the state after the Ni-P plating is formed as the thermally conductive layer 12. The size of Sample 5 is different from that of Sample 1.
[0120] In sample 5, like samples 1, 2, and 4, 15 periodic structures 11 are arranged in each of the x and y directions, so that the effective area for interaction with electromagnetic waves is 15 mm 2 x15mm 2 It is.
[0121] [Comparison between samples] Fig. 24 is a diagram summarizing the results of comparing samples. As shown in Fig. 25, in sample 1, the thermal time constant before the formation of the thermally conductive layer is 190 seconds, whereas the thermal time constant after the formation of the thermally conductive layer is faster, up to a maximum of 100 seconds. This result shows that the thermal responsiveness of the electromagnetic wave absorber 1 of the present disclosure is improved by the thermally conductive layer.
[0122] Also, it can be seen that the thermal time constant of Sample 2 is improved by the formation of the thermally conductive layer.
[0123] It is also found that the thermal time constant is improved by the formation of the thermally conductive layer in Sample 3. In Sample 3, the volume is smaller than Samples 1 and 2, and therefore the heat capacity is smaller, resulting in a smaller thermal time constant, but it is also found that the aspect ratio of the periodic structure 11 is smaller, resulting in a slightly larger reflectance.
[0124] It is also clear that the formation of the thermally conductive layer improves the thermal time constant in Sample 4. Sample 4 has an opening in a different position than Sample 1, and as a result, the reflectance is slightly higher than that of Sample 1.
[0125] It can also be seen that the thermal time constant is improved by the formation of the thermally conductive layer in Sample 5. However, compared to Samples 1 to 4, Sample 5 has the largest volume and therefore the largest heat capacity, and therefore its thermal response is the slowest.
[0126] Although the preferred embodiments of the present disclosure have been described in detail above, the present disclosure is not limited to such specific embodiments, and various modifications and / or changes are possible within the scope of the invention described in the claims. [Industrial Applicability]
[0127] The present disclosure is useful for an electromagnetic wave absorber and a method for producing the same. [Explanation of symbols]
[0128] 1. Electromagnetic wave absorber 11 Periodic structure 111 Aperture 112 Space 12 Thermal Conductive Layer 13 Metal plate 131 Adhesive layer 14 Hollow structure 141 Aperture 15 First heat conductive layer 16 Second heat conductive layer 100 Concentrator 200 structures 201 Resin layer 202 Thermal Conduction Layer 300 Heat detection unit
Claims
1. A hollow structure having a bottom surface; a heat conductive layer formed continuously from an outer surface of the hollow structure to the bottom surface; An electromagnetic wave absorber comprising:
2. The hollow structure is a periodic structure formed periodically along a predetermined plane.
2. The electromagnetic wave absorber according to claim 1.
3. The length p of one period of the periodic structure is expressed by the following formula (1), where λ is the minimum wavelength of the electromagnetic wave incident on the electromagnetic wave absorber:
3. The electromagnetic wave absorber according to claim 2. (λmin / 4)≦p≦λmin (1)
4. A height h of the periodic structure from the plane is expressed by the following formula (2), where λ is the maximum wavelength of the electromagnetic wave incident on the electromagnetic wave absorber:
4. The electromagnetic wave absorber according to claim 2 or 3. h≧(λmax / 4) (2)
5. the periodic structure is a hollow cone-shaped structure, the heat conductive layer provided on the outer surface of the hollow structure, the heat conductive layer provided on the inner surface of the hollow structure, and the heat conductive layer provided on the bottom surface are formed continuously with each other; 5. The electromagnetic wave absorber according to claim 2 .
6. The periodic structure is a pyramidal structure, and an opening is provided on a side surface of the pyramidal structure.
6. An electromagnetic wave absorber according to claim 2.
7. the periodic structure is a columnar structure having an opening on a bottom surface facing the flat surface; 5. The electromagnetic wave absorber according to claim 2 .
8. The periodic structure is a grating structure extending in a direction along the plane and in a height direction.
5. The electromagnetic wave absorber according to claim 2 .
9. The hollow structure is a spherical or cylindrical structure that reflects at least a part of an incident electromagnetic wave inside, and has an opening that allows the electromagnetic wave to enter the inside of the structure.
2. The electromagnetic wave absorber according to claim 1.
10. forming a hollow structure having a bottom surface using a 3D printer; forming a heat conductive layer continuously from an outer surface of the hollow structure to the bottom surface; Equipped with The modeling method using the 3D printer is at least one of a fused deposition modeling method, a photolithography method, a powder sintering method, and a material injection method. A method for manufacturing an electromagnetic wave absorber.
Citation Information
Patent Citations
Scanning method and recording needle rotational mechanism for cylindrical facsimile device
JP1981006572A
Electromagnetic wave absorber
JP2014187134A
Electromagnetic wave absorber
JP2015095638A
Electromagnetic wave absorption material and electromagnetic wave absorber
JP2022032341A
Light absorber, bolometer, infrared absorber, solar thermal power generation device, radiative cooling film, and method for manufacturing light absorber
JP6877770B2